Qualidade da imagem, limiar de contraste e dose glandular média em mamografia digital CR - Jakubiak, Rosangela Requi (2013)
In many countries, computed radiography (CR) systems represent the majority of equipments used in digital mammography. This study presents a method for optimizing image quality and dose in CR mammography of patients with breast thicknesses between 45 to 75mm. The breast thicknesses were simulated with polymethylmetacrylate (PMMA). Optimazed exposure parameters ((voltage (kV), mA and time product (mAs) and target/filter combination)) was defined as giving an ideal contrast to noise ratio (CNR), defined as target CNR, to reach the threshold contrast of CDMAM (version 3.4) phantom (Artinis Medical Systems, Netherlands) images for acceptable mean glandular dose (MGD). These results were used for adjustments in the automatic exposure control (AEC) by the maintenance team. A retrospective study of two groups of patients (Group 1-before AEC adjustment and Group 2- after AEC adjustment) were done. The exposure parameters were reproduced in the phantoms to determine of CNR, MGD and threshold contrast. The clinical images of these patients were analyzed by three experienced radiologists who answered questions about anatomical structures, noise and contrast in low and high pixel value areas and image sharpness and contrast. The results showed that the proposed method was effective for all breast thickness evaluated. The AEC adjustment showed a concentration of CNR in Group 2 nearer of target CNR, and that the increasing of noise in clinical images, the CDMAM analysis showed that this level of noise did not disturb the detail of 0,1 mm diameter. Finally, this study also concluded that the use AEC of X rays unit based on constant dose to the detector may bring some difficulties to CR systems operate in optimal conditions.